The correlation between measles vaccination rate of children in Poland and incidence rate of this disease from 1998 to 2017 and in Italy from 2012 to 2017 - Sokół, Dorota; Dobrzyński, Michał; Standyło, Arkadiusz; Skubel, Tomasz; Czarnota, Jakub; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Introduction. Measles is a highly contagious disease capable of inducing epidemics, which strike every 2 to 3 years. Before implementing the vaccine in 1963 measles was devastating communities leading to 135 million of victims and 6 million died because of the disease around the world. Nowadays in Europe we observe a disturbing rise of the measles incidence rate and even deaths from the disease. The epidemiologic analysis will allow to draw attention to how important and prevailing this problem is in the polish health care system.The aim of the study is to analyse the current epidemiologic situation concerning the relationship between the vaccination and incidence rate of measles in Poland from 1999-2017 and Italy from 2012-2017.Materials and methods. The data used for the epidemiologic analysis was taken from “Choroby zakaźne i zatrucia w Polsce” and “Szczepienia ochronne w Polsce” reports conducted by the National Hygiene Institute. Moreover, data from the World Health Organization reports.Results. The dropping immunization rate among children correlating with a more frequent measles outbreaks in the last years is disturbing. Immunization rate for the basic dose and booster dose for Poland is about 94% and for Italy about 92% (2017 data). Incidence rate totals respectively 8,4 per 100 thousand for Italy and 0,16 per 100 thousand for Poland.Conclusions. We need to draw parents attention to the fact that measles is still a huge and real threat. We also need to educate them that the most effective way to protect their children from getting sick is the vaccine. Moreover, awareness in society regarding the herd immunity must be increased because the contagious diseases like measles are the most dangerous to people who cannot be vaccinated.